US and euro area growth performances: Are they so different? - Bertoldi, Moreno (369 EGFR SIGNALING IMPAIRS THE ANTIVIRAL ACTIVITY OF INTERFERON-ALPHA, 2020)
The Global Financial Crisis and the European Sovereign Debt Crisis plunged the euro area into a double-dip recession cementing the narrative of a struggling Economic and Monetary Union. However, if we look at a longer time horizon that narrative is not fully justified: since its creation, with the exception of the 2011–2014 period, Euro area's per-capita GDP has actually grown as fast as the US. The critical issue behind the different growth performance of the US and the euro area over the last 20 years is related to the Sovereign Debt Crisis and the inability of Euro area institutions to counter in a timely and effective manner economic recessions. Completing the EMU architecture and adopting an appropriate policy mix will be crucial to prevent contagion and bank-sovereign feedback loops from developing in the future and ensure that the euro area grows at its potential.